Development and validation of HERWIG 7 tunes from CMS underlying-event measurements - Sirunyan, A M; Tumasyan, A; Adam, W; Ambrogi, F; Bergauer, T; Dragicevic, M; Erö, J; Escalante Del Valle, A; Frühwirth, R; Jeitler, M; Krammer, N; Lechner, L; et al. (The European physical journal. C, Particles and fields, 2021)
This paper presents new sets of parameters ("tunes") for the underlying-event model of the H E R W I G 7 event generator. These parameters control the description of multiple-parton interactions (MPI) and colour reconnection in H E R W I G 7 , and are obtained from a fit to minimum-bias data collected by the CMS experiment at s = 0.9 , 7, and 13 Te . The tunes are based on the NNPDF 3.1 next-to-next-to-leading-order parton distribution function (PDF) set for the parton shower, and either a leading-order or next-to-next-to-leading-order PDF set for the simulation of MPI and the beam remnants. Predictions utilizing the tunes are produced for event shape observables in electron-positron collisions, and for minimum-bias, inclusive jet, top quark pair, and Z and W boson events in proton-proton collisions, and are compared with data. Each of the new tunes describes the data at a reasonable level, and the tunes using a leading-order PDF for the simulation of MPI provide the best description of the data.